Biochemical changes in antioxidant pathway metabolites in Indian mustard leaves due to white rust infection - ,, Sapna; Jain, Sunita; Jain, Veena; Rathi, A.S. (Indian Phytopathology, 2011)
The activities of antioxidant pathway metabolites in leaves of white rust resistant (RH 781) and susceptible (Varuna) genotypes of Indian mustard ( Brassica juncea L.) were estimated in uninoculated and inoculated leaves during rabi (post-raining) 2007-08 at CCS Haryana Agricultural University, Hisar. Healthy leaves of resistant genotype possessed significantly more ascorbic acid content than the susceptible one. Inoculation with Albugo candida on leaves resulted in significant enhancement in ascorbic acid content in both the genotypes, however, enhancement was more in resistant genotype. Per cent glutathione (oxidized) content also increased in all the leaves in resistant genotype one day after inoculation, then-after, it decreased significantly in all the leaves, highest decline being 63.1 per cent in 3rd leaf after 3 days of inoculation. Healthy leaves of susceptible genotype showed more glutathione (reduced) as compared to resistant genotype. After inoculation, an increase in glutathione (reduced) was observed in both the genotypes; however, the increase was more in resistant genotype. The ratio of reduced to oxidized glutathione was found to be maximum (10:1) in 3rd leaf after 3 days of inoculation in resistant genotype, while, it was found to be minimum (4:1) in susceptible genotype under the similar conditions. The maximum change in levels of metabolites (ascorbic acid and glutathione) was observed after 3 days of inoculation in third leaf of both the susceptible and resistant genotypes. However, the fourth leaf (the leaf lower to the inoculated third leaf) of both the genotypes showed minimum per cent change in the activities of metabolites levels after inoculation of third leaf compared to healthy leaves as well as with respect to first, second (the leaf on the upper side to the inoculated third leaf) and third leaf (inoculated leaf) on all the days of inoculation. This might be due to the signal transduction process towards the newer leaves of the plants.